Incorporation of gold nanoparticles into Langmuir-Blodgett films of polyaniline and montmorillonite for enhanced detection of metallic ions - De Barros, A. [UNESP]; Constantino, C. J.L. [UNESP]; Bortoleto, J. R.R. [UNESP]; Da Cruz, N. C. [UNESP]; Ferreira, M. (My University, 2016)
We report on effects from incorporating gold nanoparticles (AuNPs) into Langmuir-Blodgett (LB) films of emeraldine salt polyaniline (PAni-ES) and organophilic montmorillonite clay (OMt). The synergistic electrocatalytic effect induced by AuNPs led to an enhanced performance in detecting trace levels of cadmium (Cd2+), lead (Pb2+) and copper (Cu2+) ions. Detection was carried out using square wave anodic stripping (SWAS) voltammetry using ITO electrodes modified with LB films made with three supramolecular architectures: PAni-ES/AuNPs, OMt/AuNPs and OMt/AuNPs/PAni-ES, and compared to LB films without AuNPs. The incorporation of AuNPs induced secondary doping of PAni-ES, inferred from FTIR, Raman and UV-vis. absorption spectroscopies. The PAni-ES chains probably became more extended and could intercalate into the OMt galleries, causing an increased interlayer spacing according to X-ray diffraction data. These results demonstrate the possible control of film properties by exploiting molecular-level interactions in multicomponent nanostructured films.
Keywords: Electrochemical sensors; Gold nanoparticles; Langmuir-Blodgett film; Metallic ions detection; Organophilic montmorillonite clay; Polyaniline